Identification and validation of calcium signaling pathway-related biomarkers in T1 and T2 lymph node metastatic gastric cancer - Cai, Mingzhi; Nie, Xinyang; Cai, Fenglin; Yang, Xiuding; Sun, Weilin; Zhang, Rupeng; Liang, Han; Yang, Yonglin; Zhang, Li (Frontiers in Genetics, 2025)
BackgroundLymph node (LN) status is crucial for assessing the treatment effectiveness and potential for cure in early gastric cancer (GC; T1-T2), whether treated through endoscopy or surgery. The purpose of this study was to identify biomarkers related to calcium signaling pathway in T1 and T2 lymph node metastatic gastric cancer and explore potential regulatory mechanisms.MethodsAll data applied in this study were obtained from public databases. Biomarkers were identified through univariate Cox regression analysis and survival analysis. Subsequently, enrichment analysis, somatic mutation analysis, immune microenvironment analysis, drug sensitivity analysis, and single cell analysis were used to investigate the functional mechanisms. Finally, clinical sample validation was performed.ResultsRET was identified as a biomarker through selection. Enrichment analysis indicated that 36 significantly different pathways between the NP (LN-positive samples (N1, N2, N3)) and NO (LN-negative samples (N0)) groups. A total of 2 oncogenic pathways showed significant differences between the NP and NO groups. The scores of 14 immune cell types showed significant differences, including mast cells. RET exhibited the strongest correlation with mast cells. The ESTIMATE score, stromal score, and immune score were significantly elevated in the NP group. Additionally, the NP group showed significantly higher expression of 13 immune checkpoint genes. TP53 had the highest mutation rate in both the NP and NO groups. There was a significant difference in the sensitivity to 15 chemotherapy drugs between the NP and NO groups. Additionally, RET was expressed in multiple cell types, including fibroblasts and mast cells. In both the TCGA-GC-LN and GSE84433 datasets, RET was significantly upregulated in the NP group. The RT-qPCR results of clinical samples also indicated a significant upregulation of RET in the NP group.ConclusionRET laid the foundation for targeted therapy in the treatment of T1 and T2 lymph node metastatic gastric cancer.